Pengaruh Model Pembelajaran Problem Solving Berbantuan Media Pop Up Book Terhadap Pemahaman Konsep Mata Pelajaran IPAS Topik Energi di Sekitar Kita Peserta Didik - Ni Kadek Rai Sekarini; I Ketut Sudarsana; I Komang Wisnu Budi Wijaya (Lembaga Bale Literasi, 2026)
The low level of students' conceptual understanding in science learning indicates the need for innovative learning models. This study aims to determine the effect of the Pop-Up Book-assisted Problem-Solving model on the conceptual understanding of third-grade students at Buduk 3 Public Elementary School. This study used a quasi-experimental method with a non-equivalent control group design. The sample consisted of two classes: an experimental class using the Pop-Up Book-assisted Problem-Solving model and a control class using conventional learning. Data were collected through pretests and posttests and analyzed using an Independent Sample t-test. The results showed that the experimental class' posttest average (92.23) was higher than the control class' (52.70), with a significance value of 0.000 (<0.05). Thus, the Pop-Up Book-assisted Problem-Solving model has proven effective in improving students' conceptual understanding in science learning.